Effect of nano-silica on hydration and conversion of calcium aluminate cement. (30th April 2018) - Son, H.M.; Park, S.M.; Jang, J.G.; Lee, H.K.
Highlights: Nano-silica effect on hydration and conversion of calcium aluminate cement (CAC). Nano-silica mitigated the conversion from metastable phases to stable phases. Adding nano-silica maintains the long-term strength of CAC by forming strätlingite. Abstract: This study investigated the effect of nano-silica on the hydration and conversion of calcium aluminate cement (CAC). The specimens were exposed to 60 °C to accelerate the transformation of hydrates in CAC after initial curing at 20 °C. At an early stage of curing, adding nano-silica in CAC mitigated the formation of C3 AH6 and AH3 . At 1 day after exposure to 60 °C, the compressive strength reduction was observed in all specimens, and it was closely related to the conversion of CAH10 . That is, the conversion of all specimens occurred at 28 days after exposure, which resulted in a reduction in compressive strength. However, adding nano-silica mitigated the conversion from metastable phases (CAH10 and C2 AH8 ) to stable phases (C3 AH6 and AH3 ). As a result, the extent of compressive strength loss could be reduced by the formation of strätlingite (C2 ASH8 ) in the case of 4% addition of nano-silica. In conclusion, adding nano-silica in CAC was effective regarding structural integrity by delaying the conversion of metastable hydrates, as well as maintaining the long-term strength of CAC by forming strätlingite.